The Influence of Natural Barriers on the Amphidromous Shrimp Potimirim brasiliana (Caridea, Atyidae) from Two Rivers in Southeastern Brazil - Santos, RAFAEL DE CARVALHO [UNESP]; Pantaleão, João Alberto Farinelli; Teles, Jeniffer Natalia; França, Nielson Felix Caetano; DA COSTA, Jaqueline Roberta Pereira; Cabral, Hamilton; Pardo, Luis Miguel; Mantelatto, Fernando Luis (University of Chicago Press, 2022)
The migratory behavior of freshwater shrimps may be affected by natural barriers in limnetic environments. This study evaluated the river areas separated by natural barriers, such as waterfalls, which affect the amphidromous shrimps’ (Potimirim brasiliana) population features and reproductive aspects. Results indicate that in the Félix and Pru-mirim Rivers from southeastern Brazil shrimps show few differences in sampling areas, and these differences may not be causally related to the waterfalls. This is demonstrated by the absence of a pattern in the size and sex ratio in each area and the absence of a significant difference in most reproduc- tive aspects. The presence of juveniles and reproductive individuals in all sampling areas strongly indicates a constant migration along them in both rivers, indicating that all individuals evaluated correspond to one single patchy population structure for each river. This migration conducted by P. brasiliana, such as its crawling behavior, demonstrated that it would be important to maintain the minimum number of individuals flowing between the different river sampling areas in this shrimp group. Thus, based on a helpful model observed in P. brasiliana, the results help us understand how natural barriers may affect the populations of amphidromous shrimp and how the migration behavior up-and downstream can help sustain the population. This premise can help future construction decisions and impacts of unnatural barriers, such as dams.